2011
DOI: 10.1111/j.1651-2227.2011.02383.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency and prevention: Turkish experience

Abstract: A nationwide 'vitamin D prophylaxis augmentation programme' initiated in 2005 in Turkey reduced the prevalence of rickets from 6% in 1998 to 0.1% in 2008 in children under 3 years of age. The programme included free distribution of vitamin D drops to all newborns and infants (0-12 months) visiting primary health stations throughout the country. Free disposal of vitamin D to infants is an effective strategy for preventing vitamin D-deficient rickets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
103
0
20

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(124 citation statements)
references
References 23 publications
1
103
0
20
Order By: Relevance
“…It is known that prevalence of vitamin D deficiency is remarkable during childhood and adolescence throughout the world (24,29). In Turkey, vitamin D prophylaxis is applied as the national health policy starting from the neonatal period during the first year of life, due to high vitamin D deficiency prevalence in childhood (30)(31)(32)(33)(34). In a recent study that was conducted in the same province as our study, vitamin D deficiency rate in healthy children was defined as 25%, whereas prevalence of vitamin D insufficiency was detected as 15% (31).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that prevalence of vitamin D deficiency is remarkable during childhood and adolescence throughout the world (24,29). In Turkey, vitamin D prophylaxis is applied as the national health policy starting from the neonatal period during the first year of life, due to high vitamin D deficiency prevalence in childhood (30)(31)(32)(33)(34). In a recent study that was conducted in the same province as our study, vitamin D deficiency rate in healthy children was defined as 25%, whereas prevalence of vitamin D insufficiency was detected as 15% (31).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency is the most common cause of nutritional rickets; a vitamin D level <20 ng/mL is defined as vitamin D deficiency (VDD). Until recently, rickets posed an important health problem in Turkey; however, its incidence decreased with the use of vitamin D prophylaxis (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…There were no instances of hypercalcemia, suggesting that this level of vitamin D supplementation was safe and effective for these vitamin D deficient children (Soliman et al, 2010). Results from a nationwide program in Turkey whose aim was to distribute free vitamin D drops to all newborns and infants (0-12 months) seen at primary health stations throughout the country showed that the prevalence of rickets dropped from 6% in 1998 to 0.1% in 2008 (Hatun et al, 2011).…”
Section: Infantmentioning
confidence: 94%